2007
DOI: 10.1007/s00531-007-0239-2
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow and crustal thermal structure in the Late Archaean Closepet Granite batholith, south India

Abstract: The Late Archaean Closepet Granite batholith in south India is exposed at different crustal levels grading from greenschist facies in the north through amphibolite and granulite facies in the south along a *400 km long segment in the Dharwar craton. Two areas, Pavagada and Magadi, located in the Main Mass of the batholith, best represent the granitoid of the greenschist and amphibolite facies crustal levels respectively. Heat flow estimates of 38 mW m -2 from Pavagada and 25 mW m -2 from Magadi have been obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…The arc crust is thickest towards the northern domain and becomes thinner and disrupted towards the south in the MT model, probably indicating a combined process of tectonic erosion as well as thermal and material erosion through mantle upwelling. The mantle heat flow of Madurai Block (Ray et al, 2003;Sukanta Roy et al, 2008) is much higher (23-32 mW/m 2 ) than that of other granulite provinces such as the Kapuskasing uplift region (9-13 mW/m 2 ), Voisey Bay (10-14 mW/m 2 ) of Canadian shield region; Egersund anorthosite (8-13 mW/m 2 ) of Baltic shield, among other examples, except for a similarity with that of the Kola Peninsula (25-31 mW/m 2 ) of Baltic shield (Ray et al, 2003). The markedly higher mantle heat flow values in Madurai Block when compared to adjacent Dharwar craton (11-16 mW/m 2 ) and other granulite provinces mentioned above suggests an upwelled mantle beneath the Madurai Block.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The arc crust is thickest towards the northern domain and becomes thinner and disrupted towards the south in the MT model, probably indicating a combined process of tectonic erosion as well as thermal and material erosion through mantle upwelling. The mantle heat flow of Madurai Block (Ray et al, 2003;Sukanta Roy et al, 2008) is much higher (23-32 mW/m 2 ) than that of other granulite provinces such as the Kapuskasing uplift region (9-13 mW/m 2 ), Voisey Bay (10-14 mW/m 2 ) of Canadian shield region; Egersund anorthosite (8-13 mW/m 2 ) of Baltic shield, among other examples, except for a similarity with that of the Kola Peninsula (25-31 mW/m 2 ) of Baltic shield (Ray et al, 2003). The markedly higher mantle heat flow values in Madurai Block when compared to adjacent Dharwar craton (11-16 mW/m 2 ) and other granulite provinces mentioned above suggests an upwelled mantle beneath the Madurai Block.…”
Section: Discussionmentioning
confidence: 99%
“…Seismic reflection survey from Kalugumalai to Vattalkundu in the central Madurai Block (Rajendra Prasad et al, 2007) detected generally southern dipping of reflectors with a domal pattern at the center which was thought to represent block uplift (more discussion later). Recent heat flow studies (Ray et al, 2003;Sukanta Roy et al, 2008) indicated the Southern Granulite Terrain possess large heat flow values (28-56 mW/m 2 ) when compared to Dharwar craton (25-40 mW/m 2 ) and mantle heat flow values in SGT (23-32 mW/m 2 ) are significantly higher than Dharwar craton (11-16 mW/m 2 ).…”
Section: Previous Geophysical Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Several heat flow data were added to the existing information from the Dharwar Craton and the Deccan Traps region (Fig. 2) (Roy and Rao, 2000;Roy et al, 2008). However, as can be seen from The heat flow values shown in Fig.…”
Section: Heat Flow Studiesmentioning
confidence: 98%
“…Seismic images of the compression terrains show that the rocks at depth are exposed at the surface. Thus, from surface exposures of the rocks, depth distribution of rock compositions have been worked out for several continents (Nicolaysen et al, 1981;Roy et al, 2008). Concentration of radioactive elements in exposed rocks formed under different pressure-temperature conditions provided models for depth distribution of radioactive elements under the assumption that no further differentiation of radioactive elements took place since the major crust forming events.…”
Section: Introductionmentioning
confidence: 99%